Medicinske sestre v očeh študentov zdravstvene nege - Pahor, Majda (Obzornik zdravstvene nege, 2002)
It is possible to describe the image of a profession's identity also by the ideas which others have about its members. In this article, the author looks at the Ljubljana University third year nursing students' perceptions of nursesin Slovenia. The data were collected with students' written answers to the above question. The text was analyzed using qualitative content analyis. The findings show "duality" of Slovenian nurses, perceived by the nursing students, also in connection with the central category identified which is "helping people".
Keywords: education; izobraževanje; medicinske sestre; zdravstvena nega